Peran Good Corporate Governance dalam Memoderasi Faktor-Faktor yang Memengaruhi Kinerja Keuangan - Maria Ulfa; Adelina Citradewi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Financial performance is the first face for companies that determine the willingness of investors to invest their capital. For businesses, financial performance is crucial because it serves as a gauge for assessing the health of the organization's finances. As a result, businesses need to be aware of the variables that can impact financial performance. With good corporate governance acting as a moderator, this study aims to collect empirical evidence and investigate the impact of implementing green accounting, intellectual capital, and firm size on financial performance. Companies in the energy sector that are listed on the IDX for the 2019–2021 period were the focus of this research. Purposive sampling was used in the sampling technique, and samples from 20 companies were obtained. Multiple linear regression and moderate regression analysis are the data analysis methods used. The results show that the implementation of green accounting has no effect on financial performance, intellectual capital has an effect on financial performance, and firm size has an effect on financial performance. Good corporate governance is not able to moderate the effect of implementing green accounting and firm size on financial performance, conversely good corporate governance is able to moderate the effect of intellectual capital on financial performance.